Validation and Similarity Evaluation of Leukocyte. Issue 1 (July 2021) - Deepa, P.; Deepa, D.
Abstract: Generally the Examination of WBC to identify the foreign particles, abnormal conditions and it shows the status of theleukocyte. To avoid rick factors disease of brain such as aneurism, stroke and tumor at initial stage. It also show the types, region and severity. The individual examination of basophil(B), eosinophil(E), lymphocyte(L), monocyte(M) and neutrophil(N) predetermination of patient body condition are possible in clinical level examination to get a suggestion regarding the diseases to get treated and some of the techniques are used to reduce the complexity. Automated and semi-automated tool is useful for the process. The microscopic images of different classification of leukocyte is taken from the microscopic images. Each image is evaluated, validated, compared and verified with ground truth image.